STUDI PERBANDINGAN KINERJA PENCAHAYAAN DARI RAK CAHAYA KONVENSIONAL DAN RAK PENGARAH CAHAYA PADA GEDUNG BERTINGKAT TINGGI - Vidiyanti, Christy; Bachrun, Abraham Seno (Jurnal Arsitektur dan Perencanaan (JUARA), 2022)
Daylight conditions in high-rise buildings have phenomenon that the side of the room that is close to the window have a high level of daylight, while the other side receives less daylight. The use of light shelf is still possible to be installed, but light shelf still have a minimum Useful Daylight Illuminance (UDI) value of 44%. This happens because the process of reflection on the light shelf occurs more than once. This study tries to design a light guiding shelf with the principle of reducing the amount of reflection so that the light received by the space is not reduced too much. This research will use the Sahid Sudirman Center as a case study building. The method used in this research is the experimental method. The hypothesis in this study is that buildings with light guiding shelf produce better and more uniform lighting quality than buildings with conventional light shelf. The data will be taken using the Dialux software to get data on the intensity of daylight on the building. The results showed that the conventional light shelf only had the best performance on uniformity of daylight at 12.00. While the light guiding shelf has the best performance on all criteria, that sDA350-6650, light uniformity, light contrast and DGP at 08.00 and 16.00. In addition to being able to meet the best daylighting quantity performance, the light guiding shelf is also able to produce good daylighting quality performance. So overall, light guiding shelf has better lighting performance than conventional light shelf, so the hypothesis in this study is accepted.Â